DESIGNING AN ANIMAL ADOPTION AND SOCIAL MEDIA INFORMATION SYSTEM USING THE SDLC WATERFALL METHOD - Fabriyan Fandi Dwi Imaniawan; Dany Pratmanto; Teguh Rijanandi; Ayu Silvia (Jurnal Teknoinfo, 2023)
Animal lovers are not only known as people who like certain animals because of their uniqueness or cuteness. Behind it all, animal lovers have the privilege that they are called good people. This is not without reason, because of course people who like to keep animals must be full of affection, sensitive and they have a way to be happy. We often have problems if we are animal lovers, we don't know where the nearest vet is, especially if we are a newcomer from a faraway city, where can we buy equipment or pet food, and the worst is if we don't know how to care for animals. our pets, especially when our pets are sick or other examples if we want to adopt animals or want to release our adopted animals to other people through existing social media but we are afraid of being deceived or even our pets will be abandoned. With the rapid development of this technology and with the help of artificial intelligence technology, we want to overcome all these problems, because technological developments have been used in all aspects such as schools, hospitals and so on. No exception in the field of animal and animal husbandry. We want to design an adoption information system using the Software Development Life Cycle (SDLC) method which is divided into several stages such as analysis, design, implementation, verification and finally repair. The author uses qualitative methods to collect data which the author will discuss on the background and stages of system analysis in the waterfall development method, qualitative methods emphasize more on observing phenomena and examining more into the substance of the meaning of these phenomena. The analysis and acumen of qualitative research are greatly affected by the strength of the words and sentences used. The system design we created uses the PHP Programming Language, Javascript and the mysql database, the authors hope that this research can become a reference for other articles in the future.